The Effect of Digital Multilingual Thematic Dictionary Toward The Fifth Grade Students' Literacy Skill - Mella Resita Widhiastari; Ni Made Ratminingsih; I Gede Budasi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research aimed to discover whether using a digital multilingual thematic dictionary significantly affects fifth-graders' literacy skills. The author applied pre- and post-test control groups alone for its quasi-experimental design. The researcher used a multi-stage sampling technique to select the research sample. The stage consist of three steps namely: (1) determining population; (2) placement of the sampling area using the statistical matching technique proposed by Fraenkel, J.R., Wallen, N.E., and Hyun, H.H. (2012); and (3) selection of the control and experimental groups via lottery. Students in the 5A grade from SD N 1 Seririt served as the control group and fifth-graders from SD N 1 Kubutambahan served as the experimental group for the sample. The research instruments featured teaching scenarios for the control and experimental groups as well as literacy competency exams with pre- and post-test questions. The pre-test was administered before of treatment, and the post-test was done afterwards. Three treatment sessions were provided to each group using three different treatment lesson materials namely: daily activities, my school, and clothes. The acquired data were quantitatively examined using N-Gain score test analysis, inferential statistics, and descriptive statistics. Based on the findings of the N-Gain Score test computation and the descriptive analysis, the experimental group's mean N-Gain score was 70.5453%, whereas the control group's mean N-Gain score was 67.9676%. The use of multilingual thematic printed dictionaries in the control group and multilingual thematic digital dictionaries in the experimental group shared the same effect, particularly regarding that they were